Renewables Obligation (Scotland) : consultation on implementing an exemption for energy intensive industries from the indirect costs of the Renewables Obligation Scotland : 19 May 2016 – 30 June 2016.: consultation on implementing an exemption for energy intensive industries from the indirect costs of the Renewables Obligation Scotland : 19 May 2016 – 30 June 2016. (2016) - Unknown
No abstract available